Design of automatic aircraft parking system module visually guidance display using ESP32 Microcontroller as practical media - Nurwijayanti Kusumaningrum; Yogi Setiawan (Compiler, 2022)
A visual guidance display is a module that was created to assist the pilot task when parking his plane or helping to control aircraft parking at the airport. Up to now, the pilot task is still assisted by a parking attendant (Marshaller) whose aim is to guide the movement of the aircraft to the parking lot. So, a practicum module was made as a medium of learning and knowledge along with the use of alternative technology. This module uses a Visual Guidance Display (automatic aircraft parking aid). This module design uses 3 32x8 pixel dot matrix display boards with dimensions of 13x3.5 cm which are combined into one to form an appropriate combination to produce a parking direction display. The display used is a super right led dot matrix. The controller is an ESP32 microcontroller and a series of shift registers to display the right, left, straight, and stop motion views as well as the distance display of the aircraft to the parking stop point on the apron.